COVID-19 DAN KEBEBASAN BEREKSPRESI DI INTERNET: MELIHAT REPRESI DIGITAL DALAM PEMBERITAAN TEMPO.CO - Muhammad Iqbal Khatami; Moch. Edward Trias Pahlevi (Universitas Teuku Umar, 2022)
The presence of the Covid-19 pandemic and high internet penetration in Indonesia have also encouraged community activities, one of which is digital activism. The purpose of this article is to describe digital activism carried out in the midst of a pandemic that has received a lot of repressive measures in cyberspace. The approach used is media cloud content analysis of Tempo.co news related to digital repression in Indonesia from March to December 2020. Researchers processed data using Nvivo 12 Plus software, the data generated included crosstab and wordcloud analysis. The results showed that hacking and doxing attacks were the most discussed cases of digital repression on Tempo.co. In addition, law enforcement and law enforcement against democracy in danger are indicators of the highest issue in Tempo.co's reporting. While the wordcloud analysis shows quotes from the police and government, many words imply some form of performance from the Police and Government.